A Security Enhancement to The Secure Mutual Authentication Protocol for Fog/Edge - Azzahra, Arsya Dyani; Lestari, Andriani Adi; Siswantyo, Sepha; Handayani, Annisa Dini; Farida, Yeni; Priambodo, Dimas Febriyan (Prodi Pendidikan Teknik Informatika Universitas Pendidikan Ganesha, 2025)
A secured mutual authentication protocol (SMAP Fog/Edge) has been developed for fog computing. The protocol provides secure mutual authentication which lightweight and efficient for fog computing environments. However, based on AVISPA’s verification from Azzahra research, this protocol has been found to be vulnerable to man-in-the-middle (MITM) attacks due to the absence of an authentication scheme between authentication server and the edge user. The attacks are carried out assuming that the public key of the fog server is not distributed over a secure channel. Rhim research and Lestari research successfully enhance the security level with digital signature. In line with that, we propose modified mechanism that utilizes encryption and digital signatures to substitute the secure channel for distributing the public key of the fog server and authenticating edge users by the authentication server. All modification is using authentication server for digital signature to enhance the security of SMAP Fog/Edge and make it resistant to man-in-the-middle attacks. The proposed protocol is revalidated using the AVISPA tool to determine whether the vulnerability still exists. The result indicates prototype successfully resistant to MITM